2017
DOI: 10.1021/acs.orglett.7b02261
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Discovery Using Neopentylene-Tethered Coupling Partners: Cycloisomerization/Oxidation of Electron-Deficient Dienynes

Abstract: A rhodium-catalyzed cycloisomerization and oxidation of tethered dienynes for the synthesis of indanes is described. An auxiliary fragmentation/olefination method (also described herein) provides novel access to tethered alkyne-dienoate substrates. The reported method circumvents current limitations in and expands the scope of inverse-demand Diels-Alder-type cycloadditions. Traditional discovery substrates involving malonate-, ether-, and sulfonamide-based tethers are problematic in the current methodology, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…We have a broader interest in developing concise synthetic approaches to illudalane sesquiterpenes, but the immediate priority was to gain rapid access to material to support pharmacological studies. Therefore, we developed an expeditious synthesis of illudalic acid that leverages our recent oxidative cycloisomerization methodology along with insights from the previous syntheses of illudalic acid. , As outlined in Scheme , we envisioned converting neopentylene-fused benzoate 1 (available in four steps from dimedone and already under production in the Dudley lab) to linear hydrindacene 2 , an advanced intermediate from the Woodward and Shen syntheses, and ultimately to illudalic acid ( IA-30 ), with methyl ether IA-25 serving as the final synthetic precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have a broader interest in developing concise synthetic approaches to illudalane sesquiterpenes, but the immediate priority was to gain rapid access to material to support pharmacological studies. Therefore, we developed an expeditious synthesis of illudalic acid that leverages our recent oxidative cycloisomerization methodology along with insights from the previous syntheses of illudalic acid. , As outlined in Scheme , we envisioned converting neopentylene-fused benzoate 1 (available in four steps from dimedone and already under production in the Dudley lab) to linear hydrindacene 2 , an advanced intermediate from the Woodward and Shen syntheses, and ultimately to illudalic acid ( IA-30 ), with methyl ether IA-25 serving as the final synthetic precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl 4,7-Dibromo-2,2-dimethyl-2,3-dihydro-1H-indene-5carboxylate (3). To a stirred suspension of AlCl 3 (8.40 g, 62.8 mmol, 2.5 equiv) in DCM (40 mL) at 0 °C was added neopentylenefused benzoate ester 1 19 (5.48 g, 25.1 mmol) in dry DCM (10 mL) dropwise. After stirring for 30 min, Br 2 (2.8 mL, 55.2 mmol, 2.2 equiv) was slowly added to the mixture.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Like 1,6-diyne 3 (Scheme ), NPT enynes are attractive building blocks for chemical synthesis. We have shown how NPT enynes derived from dimedone can advance synthetic methodology, streamline previous syntheses of hirsutene and illudol, support concise syntheses of alcyopterosin A and illudinine, and facilitate production of synthetic illudalic acid and analogues . Our approach to illudinine begins with tandem fragmentation and Knoevenagel-type condensation of 6 with 7 to prepare pyridyl enynes 8 then cycloisomerization to access isoquinoline systems en route to the natural product (Scheme , bottom).…”
Section: Introductionmentioning
confidence: 81%
“…Dudley et al reported a breakthrough methodology for Rhpromoted Diels-Alder-type reaction of tethered alkyne-dienoate substrates, including ether 21: the reaction was performed at room temperature using a cationic rhodium(I) norbornadiene catalyst (10 mol%) together with silver hexafluoroantimonate (20 mol%) as additive, followed by treatment with DDQ. 23 The authors hypothesized an initial coordination of Rh(I) to the -system, followed by cyclization to rhodium(III) intermediate 22 and reductive elimination to regenerate Rh(I) and release 23, which is later oxidized to corresponding phthalan 24 (Scheme 9). Scheme 9 Rh-promoted formal IMDA of tethered alkyne-dienoate substrates Liang and coll.…”
Section: Several Procedures For Phthalans Synthesis Based On Cyclizationmentioning
confidence: 99%